Results of a Virtual Migraine Education Program in an Employed Population. Issue 1 (January 2022) - Burton, Wayne N.; Schultz, Alyssa B.; Shepherd, Martha E.; McCluskey, Maureen; Hines, David
Abstract : Objective: Migraine affects about 15% of the world's population and disproportionately affects adults who are working age. It is associated with higher healthcare costs, absenteeism, and lost productivity. A metropolitan school district in the southern United States offered a virtual migraine education program to their teaching employees. Methods: Seventy-nine employees completed a migraine questionnaire at both baseline and 3-month follow-up. The program included webinars, educational videos, and other intranet-based resources. Results: Results found that program participants reported a significant improvement in the frequency and severity of migraine as well as a reduction in lost on-the-job productivity. A majority of participants reported making positive changes to reduce triggers and better manage stress. Conclusions: An employer-offered migraine education program distributed virtually to remote workers has the potential to improve migraine symptoms and treatment as well as productivity.